A novel cuproptosis-related lncRNA prognostic risk score model for gastric cancer based on bioinformatics. (13th September 2022) - Du, Xue; Xiao, Yu; Chen, Chunbao; Yang, Lu; Cui, Yu; Wu, Tingting; Tan, Bangxian
Objective: To establish an effective cuproptosis-related long non-coding ribonucleic acid (lncRNA) (CRL) prognostic risk score (RS) model (CRLPRSM) for the prediction of the outcomes of patients with gastric cancer (GC). Introduction: Cuproptosis is an up-to-date mode of cell death, and its action mechanism is different from all other known mechanisms that regulate cell death. LncRNAs are RNA species that are over 200 nt long and do not encode proteins. They have prominent actions in tumor onset and development, and their involvement in a variety of intracellular regulatory processes is vital for cell proliferation and differentiation, so they may serve as prognostic biomarkers in tumor patients. Methods: We retrieved cuproptosis-associated clinical and lncRNA expression data of GC cases from The Cancer Genome Atlas Stomach Adenocarcinoma (TCGA-STAD). Then a CRLPRSM was built based on univariate and multivariate Cox regression (UCR and MCR) analyses. As per the RS, the patients fell into high- and low-risk group. Later, the predictive efficacy of the CRLPRSM was confirmed with the aid of Kaplan-Meier (KM) analysis and receiver operating characteristic (ROC) curve analysis. Next, combining independent prognostic factors in clinical characteristics, we plotted a prognosis-related nomogram to predict one-year, three-year and five-year overall survival (OS) in GC patients. Finally, we implemented Gene Ontology enrichment analysis (GOEA) and Kyoto Encyclopedia of Genes and Genomes enrichment analysis (KEGGEA) for clarifying the possible biological actions and molecular mechanisms. Results: The constructed CRLPRSM consisted of 3 CRLs, namely, AC092574.1, MAGI2-AS3, AC090204.1. It was found that the hazard ratio (HR) was 1.911 (1.337–2.731) ( p < 0.001) in UCR analysis and 1.852 (1.286–1.668) ( p < 0.001) in MCR analysis, and the AUC of the CRLPRSM was 0.649. Moreover, the KM analysis showed a pronounced intergroup difference in survival, and the nomogram illustrated some clinical benefits of CRLPRSM. Furthermore, GO terms and KEGG pathways were unveiled to be significantly enriched. Conclusion: The constructed CRLPRSM has a significant predicted value for GC patient prognosis, and CRLs may become novel hallmarks for clinical treatment of GC.